Examining the competitiveness of the Great Plain region through a few basic indicators - Rőfi, Mónika (Acta Agraria Debreceniensis, 2006)
There are significant differences in the level of economic development and social relations between the various regions of Hungary, consequently, their competitiveness is also dissimilar. The term ’competitiveness’ has recently gained a regional meaning from various aspects. The unified interpretation of ’competitiveness’ is applicable to all basic units of the economy in a flexible way, and is therefore applicable on regional level as well. Regional competitiveness is measured against four economic categories: regional income per capita, work efficiency, employment rate and age composition. In addition to an overview of the region, this study will analyse the above components of regional competitiveness based on data describing the region.